Sovereign Words: Indigenous Art, Curation and Criticism - García-Antón, Katya (Office for Contemporary Art Norway, 2018)
Artists and cultural practitioners from Indigenous communities around the world are increasingly in the international spotlight. As museums and curators race to consider the planetary reach of their art collections and exhibitions, this publication draws upon the challenges faced today by cultural workers, Indigenous and non-Indigenous, to engage meaningfully and ethically with the histories, presents and futures of Indigenous cultural practices and world-views. Sixteen Indigenous voices convene to consider some of the most burning questions surrounding this field. How will novel methodologies of word/voice-crafting be constituted to empower the Indigenous discourses of the future? Is it sufficient to expand the Modernist art-historical canon through the politics of inclusion? Is this expansion a new form of colonisation, or does it foster the cosmopolitan thought that Indigenous communities have always inhabited? To whom does the much talked-of 'Indigenous Turn' belong? Does it represent a hegemonic project of introspection and revision in the face of today's ecocidal, genocidal and existential crises?"–Page 4 de la couverture. Autres auteurs/titres:edited by Katya García-Antón ; contributors, Daniel Browning, Kabita Chakma, Megan Cope, Santosh Kumar Das, Hannah Donnelly, Léuli Māzyār Luna'i Eshrāghi, David Garneau, Biung Ismahasan, Kimberley Moulton, Máret Ánne Sara, Venkat Raman Singh Shyam, Irene Snarby, Ánde Somby, Megan Tamati-Quennell, Prashanta Tripura, Sontosh Bikash Tripura.
Section: 287 pages : illustrations (principalement en couleur) ; 24 cm.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Oubliées ou disparues : Matérialiser absences et mémoires - Graff, Julie (ICOFOM Study Series, 2020)
L’exposition Öndia’tahterendih, oubliées ou disparues : Akonessen, Zitya, Marie et les autres, créée par la Boite Rouge Vif, une OBNL autochtone du Québec, et la commissaire wendate Sylvie Paré, présente 10 artistes rendant hommage aux femmes et aux filles autochtones touchées par le féminicide autochtone, tout en cherchant à mobiliser le public. Je souhaite dans le cadre de cet article explorer les stratégies mises en place au sein de l’exposition, telle qu’elle a été présentée au musée de la Civilisation du Québec en 2018. Je conclurai en explorant l’inscription de l’exposition dans le développement d’un commissariat engagé autochtone au Canada.
ISBN: 9782491997113 Number: 48-1
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé